The Principle of Distrust to Thoughts and the Problem of the Correlation of Epistemic and Moral Responsibility (on the Example of Articles by A.S. Mishura and S.M. Levin) - S. R. Murtazin (Дискурс)
Introduction. The article is devoted to the problem of the correlation between moral and epistemic responsibility. As a concrete example of the concept that takes into account the interrelation between the two forms of responsibility under consideration, the 'principle of distrust of thoughts' formulated in the articles by A.S. Mishura and S.M. Levin is given. The aim of the article is to analyze this principle and the arguments in its favor, as well as to clarify the distinction between moral and epistemic responsibility.Methodology and sources. The author uses the method of conceptual analysis to solve the research problem. The main sources of the work are articles by A.S. Mishura and S.M. Levin. Auxiliary sources include the works of authors belonging to the analytic philosophical tradition.Results and discussion. The article analyses two possible forms of responsibility: epistemic and moral. Two possible types of definitions of the word «responsibility» are considered. Descriptive ones involve the formulation of conditions necessary for the possibility of reacting to the agent's actions or beliefs. Prescriptive ones involve criteria for judging an agent, their actions, or their beliefs as deserving of reward or blame. The principle of thought disbelief, advocated by A.S. Mishura and S.M. Levin, suggests that in certain situations it is morally responsible to reject evidence in favor of the truth of certain beliefs. The weakness of the articles analyzed is that the examples do not help to clarify the causal link between a true belief and a morally corrupt act.Conclusion. The article doubts that A.S. Mishura and S.M. Levin have been able to demonstrate clearly and convincingly the relationship between an agent's true beliefs and their morally corrupt actions. In the author's view, the examples given by S.M. Levin could be reduced to a choice between alternative interpretations of moral responsibility, rather than a choice between moral and epistemic responsibility.